2006
DOI: 10.1086/500314
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Weak MgiiAbsorbing Structures

Abstract: We consider geometries and physical models for weak low-ionization absorbers based on the relative incidence of low-and high-ionization systems. We present a survey of weak low-ionization systems in 35 high-resolution HST STIS quasar spectra, sometimes supplemented by Keck HIRES and HST FOS data. We found 16 metal-line systems, with low-and/or high-ionization absorption detected. Weak low-ionization absorbers trace an abundant population of metal-enriched regions. Models show that these systems have a $10 pc r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…These absorbers are expected to trace neutral and ionized gas in the discs of galaxies and their gaeous halos (including HVCs). The so-called weak Mg ii systems have W 2796 ≤ 0.3 Å; they appear to be less tightly associated with galaxies and are typically found at larger distances from luminous galaxies, in the range 35−100 h −1 kpc (Milutinović et al 2006;Rigby et al 2002). are related to discs, disc-halo interfaces, and galactic winds (e.g., Bouché et al 2012).…”
Section: Covering Fraction Of Strong Mg II Absorption In the Milky Wamentioning
confidence: 99%
See 1 more Smart Citation
“…These absorbers are expected to trace neutral and ionized gas in the discs of galaxies and their gaeous halos (including HVCs). The so-called weak Mg ii systems have W 2796 ≤ 0.3 Å; they appear to be less tightly associated with galaxies and are typically found at larger distances from luminous galaxies, in the range 35−100 h −1 kpc (Milutinović et al 2006;Rigby et al 2002). are related to discs, disc-halo interfaces, and galactic winds (e.g., Bouché et al 2012).…”
Section: Covering Fraction Of Strong Mg II Absorption In the Milky Wamentioning
confidence: 99%
“…However, compared to strong Mg ii systems, weak Mg ii absorbers probably are located at larger distances from the galaxies, i.e., in their circumgalactic environment (Milutinović et al 2006). For the same line of arguments outlined in the previous section, the contribution of the 21 cm HVCs at d < 60 kpc to the number density of weak Mg ii absorbers must be small.…”
Section: On the Contribution Of Hvcs To The Absorber Density Of Weak mentioning
confidence: 99%
“…The QSO Mg II EW distribution shows a clear turnover around W r ∼ 0.3Å, hinting at different populations (e.g., Churchill et al 1999;Nestor et al 2005;Milutinović et al 2006;Narayanan et al 2007, hereafter N07). Here we show for the first time that, contrary to the strong systems, the weak (W r < 0.3Å) and the moderately strong (0.3 ≤ W r < 1Å) Mg II statistics conform to those derived from QSO surveys.…”
Section: Introductionmentioning
confidence: 99%
“…This thin region that produces Mg ii absorption is most likely surrounded by a lower density region that produces high-ionization C iv absorption, with both regions centered at the same velocity (Rigby et al 2002). Components offset in velocity by tens of km s À1 also often exist in C iv and could represent additional surrounding low-density filaments (Milutinović et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Narayanan et al (2005) used E140M Space Telescope Imaging Spectrograph Hubble Space Telescope archive data to search for Si ii k1260 and C ii k1335 as tracers of Mg ii, and found a number density of absorbers dN /dz ¼ 1:00 AE 0:20. Churchill et al (1999) used the High Resolution Spectrograph on the Keck I Telescope and observed the Mg ii kk2796, 2803 doublet directly, finding dN /dz ¼ 1:74 AE 0:10.…”
Section: Introductionmentioning
confidence: 99%